Traditional Cake Ethnomathematics-Based Learning Video on Introductory Material of Geometric Shapes for First-Grade Elementary School - Fitriah, Lailatul; Nuraini, Ni Luh Sakinah; Yuniawatika (MIMBAR PGSD Undiksha, 2024)
Learning mathematics is a challenge that is often faced by students at various levels of education because learning mathematics tends to be too theoretical, less contextual, and varied so students' interest in learning mathematics decreases. Lack of context in learning mathematics that links students' culture and everyday life so students have difficulty understanding the material. This study aims to produce ethnomathematics-based learning videos that use traditional cakes as a learning context for spatial recognition material for first-grade elementary school students. The traditional cake was chosen as a culturally relevant context to introduce students to the basic concepts of geometric shapes. The ADDIE development model was used with data collection instruments using observation and interviews with teachers and students. The research subjects included media experts, material experts, users, and first-grade elementary school students who were declared very valid with the results of the media expert test score of 100%, material experts 90.9%, and users 100%. Product practicality based on small-scale trials gets a percentage of 100% and large-scale gets a percentage of 97% for first-grade elementary school students. From these results, it can be stated that traditional cake ethnomathematics-based learning videos are interesting and practical to use.